Local Government Behavior in Implementing the Constitutional Rights of Communities Affected by Natural Disasters: A Legal Analysis State's Affairs on Disaster Management - Sutri Helfianti; Iskandar Iskandar; Mudhafar Anzari; Musradinur Musradinur; Aisyah Aisyah (Rechtsvinding, 2026)
Study This motivated by problems gap systemic between guarantee right constitutional public affected disaster natural in the 1945 Constitution with implementation by the government area, which is marked with overlapping overlap regulation, behavior discretion problematic, fragmentation institutional, deficit accountability, as well as ineffectiveness mechanism accountability law. Type study This is study law normative with approach studies library research that analyzes material primary, secondary, and tertiary law in a way descriptive qualitative. Research results show that runway juridical right constitutional rights of disaster victims nature piled up but No integrated, creating uncertainty law. Behavior patterns government area be on the spectrum from response progressive until discretion problematic violations Principles General Good Governance. Roots failure implementation lies in disharmony regulation, fragmentation institutional and deficit accountability that forms circle demon systemic. Mechanism accountability existing laws, both preventive and repressive, proven No adequate For restore fundamental rights of disaster victims. Research conclusions This is that behavior government problematic areas is reflection from governance design disasters that are structural No side with protection right constitutional community. Implementation results study recommend fundamental reforms in realm regulations through compilation standard national indicator fulfillment right disaster victim base, strengthening authority BPBD coordination accompanied by real-time audits, as well as formation Constitution special about not quite enough state responsibility in disaster with procedure lawsuit simple.